2019
DOI: 10.1210/en.2019-00144
|View full text |Cite
|
Sign up to set email alerts
|

Human Trophoblast Differentiation Is Associated With Profound Gene Regulatory and Epigenetic Changes

Abstract: Defective placental implantation and vascularization with accompanying hypoxia contribute to preeclampsia (PE), a leading cause of maternal and neonatal morbidity and mortality. Genetic and epigenetic mechanisms underlying differentiation of proliferative cytotrophoblasts (CytTs) to multinucleated syncytiotrophoblast (SynT) are incompletely defined. The SynT performs key functions in nutrient and gas exchange, hormone production, and protection of the fetus from rejection by the maternal immune system. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 70 publications
4
21
0
Order By: Relevance
“…6). Our findings also support a recent study, which showed that CTB to SynTB differentiation is associated with increased RNA-POL-II binding to promoters of a subset of genes (83). However, we found that GATA2 is also expressed in the undifferentiated BeWo cells.…”
Section: Discussionsupporting
confidence: 92%
“…6). Our findings also support a recent study, which showed that CTB to SynTB differentiation is associated with increased RNA-POL-II binding to promoters of a subset of genes (83). However, we found that GATA2 is also expressed in the undifferentiated BeWo cells.…”
Section: Discussionsupporting
confidence: 92%
“…While genetic contributions to different complications in pregnancy are probably polygenic, genome-wide association studies (GWASs) have found genetic variants associated specifically with sPTB, illustrating how a mother's genetic makeup can set the stage for fetal development and pregnancy outcome even before conception [71][72][73]. By contrast, maternal epigenetic modifications reflect the state of different cell types across tissues as they reprogram to prepare for fetal growth [74,75]. Quantification of these modificationsby measuring DNA methylation, histone markers, and chromatin accessibility in the cell subsets of interestoffers insights into whether different cell types in the maternal-fetal interface are adapting properly for a successful pregnancy [76,77].…”
Section: Genetics and Epigenetics For Characterizing Pregnancymentioning
confidence: 99%
“…Recent derivation of human trophoblast stem cells was made possible, in part, by using an HDAC inhibitor to maintain cells in a stem state, suggesting a critical role for HDAC activity in human trophoblast differentiation 25 . Indeed, differentiation of primary human cytotrophoblasts is associated with profound changes in histone acetylation, including gene-and promoter-specific changes in H3K9 and H3K27 acetylation 26 . Collectively, these studies emphasize the critical role of histone acetylation dynamics and HDAC activity in the regulation of trophoblast differentiation and placental development, which prompted us to investigate the functional role of specific HDACs during human syncytiotrophoblast formation.…”
Section: Introductionmentioning
confidence: 99%